Inter-system and inter-unit reliability of Polar Team Pro and WIMU PRO devices during external load measurements indoors - Rodríguez-Fernández, A.; Suárez-Iglesias, D.; Vaquera, A.; Leicht, A. S.; Rodríguez-Marroyo, J. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The aim was to examine inter-system and inter-unit reliability of both WIMU PRO (UWB) and Polar Team Pro devices in measuring indoor sport-specific movements. Seventeen active and healthy adults (age: 21.4 ± 5.2 years; height 170.3 ± 8.2 cm; body mass: 71.2 ± 4.5 kg) completed one repetition of an indoor team sport circuit (i.e. accelerations, decelerations, change of direction, jumps and arc runs). Participants carried two 10-Hz Polar Team Pro GPS and wore two 20-Hz GPS (UWB) WIMU PRO chest- and back-mounted devices, respectively. Distance (absolute, relative and in different speed thresholds), mean and peak speed, accelerations and decelerations at different intensities and jumps were recorded. A repeated-measures two-way analysis of variance and ICC and CV were utilised. There was a significant (p = 0.001) main effect of the system for all variables except the total distance, mean speed and distance covered during low- and high-intensity running. There were significant differences (p < 0.05) between the two Polar Team Pro units for all external load variables except for distance covered during submaximal speed, moderate-intensity accelerations (ACC), and moderate-intensity and total decelerations (DCC). No significant differences (p > 0.05) between the two WIMU PRO units were detected. Poor inter-system reliability was ascertained, with inter-unit reliability being moderate-excellent for most variables of both systems.